T-Cell Immunophenotyping Distinguishes Active From Latent Tuberculosis - Pollock, Katrina M.; Whitworth, Hilary S.; Montamat-Sicotte, Damien J.; Grass, Lisa; Cooke, Graham S.; Kapembwa, Moses S.; Kon, Onn M.; Sampson, Robert D.; Taylor, Graham P.; Lalvani, Ajit (The Journal of infectious diseases, 2013)
Background. Changes in the phenotype and function of Mycobacterium tuberculosis (M. tuberculosis)-specific CD4⁺ and CD8⁺ T-cell subsets in response to stage of infection may allow discrimination between active tuberculosis and latent tuberculosis infection. Methods. A prospective comparison of M. tuberculosis-specific cellular immunity in subjects with active tuberculosis and latent tuberculosis infection, with and without human immunodeficiency virus (HIV) coinfection. Polychromatic flow cytometry was used to measure CD4⁺ and CD8⁺ T-cell subset phenotype and secretion of interferon γ(IFN-γ), interleukin 2 (IL-2), and tumor necrosis factor α (TNF-α). Results. Frequencies of CD4⁺ and CD8⁺ cells secreting IFN-γ-only, TNF-α-only and dual IFN-γ/TNF-α were greater in active tuberculosis vs latent tuberculosis infection. All M. tuberculosis-specific CD4⁺ subsets, with the exception of IL-2-only cells, switched from central to effector memory phenotype in active tuberculosis vs latent tuberculosis infection, accompanied by a reduction in IL-7 receptor α (CD127) expression. The frequency of PPDspecific CD4⁺ TNF-oc-only-secreting T cells with an effector phenotype accurately distinguished active tuberculosis from latent tuberculosis infection with an area under the curve of 0.99, substantially more discriminatory than measurement of function alone. Conclusions. Combined measurement of T-cell phenotype and function defines a highly discriminatory biomarker of tuberculosis disease activity. Unlocking the diagnostic and monitoring potential of this combined approach now requires validation in large-scale prospective studies.